Implementation of Digital Libraries in Increasing Reading Interest at the Brida Literacy Corner, Medan City - Aruan, Nuraini Br; Andrianni, Naniah; Shabirah, Najla; Bagus, Muhammad Dwi; Kurniawan, Fahmi; Tambunan, Toman Sony (Lembaga Riset Mutiara Akbar, 2024)
The implementation of the literacy movement of reading corners and libraries that is less than optimal causes a lack of interest in reading in the general public in reading. the use of libraries has not been running as it should until now. The digital literacy movement is attempted by encouraging the general public to get used to reading BOOKS and carrying out digital literacy activities. The main program of RESEARCH of Panca Budi Medan Development University aims to empower the improvement of literacy in the general public, The digital era is a time when humans live side by side with the development of digital technology which is the progress of civilization for humans themselves. In the digital era, there are many disruptions that occur in the midst of people's lives, including literacy media that have changed from print to digital, but the rapid flow of information and valid sources of information have become a challenge in digital literature, therefore in order to support motor development, reading interest, and efforts to expand knowledge through reading media, we initiated our program related to digital media literacy through the